INVESTIGATING TEACHERS PERCEPTION OF THE REASSONS OF LEARNING DISABILITIES IN ENGLISH LANGUAGE - Al-Khawaldeh, Mohammad Abedrabbu; khasawneh, Mohmmad (Imagens da Educação, 2022)
This study aimed at identifying the English language teachers’ perspectives toward learning disabilities, in addition to the teachers’ suggestions for treating learning difficulties in English language to raise the achievement level of students. To achieve the objectives of the study, interviews were conducted with primary school teachers to identify more reasons and suggestions from their point of view on how to treat students’ learning difficulties in English. The results indicated that there were statistically significant differences in the estimates of primary school teachers for the reasons for students’ LDs in English language in several fields among the students. The study concluded with recommendations on the need to diversify in teaching methods, reduce the teaching burden for teachers from lessons, and open channels of communication between home and school to follow up on students’ affairs. The study also recommended identifying all the problems students face in the process of learning the language and increasing the awareness of students and their families about the importance of learning English language. In addition, schools should be encouraged to establish a special laboratory for English language, equipped with the latest tools to enable students to listen to the language better and with sound pronunciation, and encouraging teachers to develop remedial plans to improve the achievement level of students.